Tipologi Kepemimpinan Perempuan Aceh (Studi Gender dan Feminisme) - Ismawardi, Ismawardi (Jurnal Sosiologi USK (Media Pemikiran & Aplikasi), 2018)
Women's leadership is nothing new for the Acehnese. In the history of Aceh, some women have emerged as leaders. As time pass by, some Acehnese women are entrusted to occupy several strategic positions ranging from lower to upper levels. To find out more about women's leadership in Aceh, the author seeks to learn the typology of Acehnese women leadership. This study aims to examine the efficacy and achievement of the women in leading governmental institutions by taking into account each type or style of leadership performed and the driving factors of their success. This study uses an interpretive descriptive approach with data collection techniques through interviews, observation, and documentation. The study showed that some factors contributed to the ability of women in leadership such as family, education, and the environmental condition. The types of women's leadership in Aceh are charismatic, democratic, bureaucratic, participatory, transformational, and cultural. There are some other factors that contribute to women's leadership in Aceh; First, the public is confidence and perceives female leaders. Second, their involvement in organizational activities. Third, the family's emotional connection also plays a role in developing their characters.Keywords: Typology, Womens, LeadershipKepemimpinan perempuan bukanlah hal yang baru di mata masyarakat Aceh. Dalam sejarah kesultanan Aceh, beberapa perempuan telah menjadi pemimpin dan hingga saat ini beberapa perempuan Aceh masih dipercaya untuk menduduki beberapa jabatan strategis, mulai dari level bawah hingga level atas. Untuk mengetahui lebih jauh tentang kepemimpinan perempuan Aceh, penulis mencoba menelaah melalui sebuah penelitian terkait dengan tipologi kepemimpinan perempuan Aceh. Penelitian ini bertujuan untuk melihat kemampuan dan keberhasilan perempuan dalam memimpin sebuah lembaga dengan masing-masing tipe atau gaya kepemimpinan yang dimiliki serta faktor-faktor yang mempengaruhi keberhasilan tersebut. Penelitian ini menggunakan menggunakan pendekatan deskriptif interpretatif dengan teknik pengambilan data melalui wawancara, observasi dan dokumentasi. Berdasarkan hasil penelitian, kemampuan kepemimpinan perempuan Aceh dipengaruhi oleh beberapa faktor diantaranya adalah faktor keluarga, pendidikan, dan kondisi lingkungan. Adapun tipe kepemimpinan yang dimiliki oleh pemimpin perempuan di Aceh adalah kharismatik, demokratis, birokratis, partisipatif, transformatif, dan kulturalis. Adapun faktor lain yang mempengaruhi adalah, pertama adanya kepercayaan masyarakat terhadap pemimpin perempuan. Kedua, kemampuan memimpin perempuan Aceh juga tidak terlepas dari pengaruh keaktifan perempuan dalam berorganisasi. Ketiga, Kepemimpinan perempuan Aceh juga diwarisi dari hubungan emosional keluarga.Kata Kunci: Tipologi, Kepemimpinan, Perempuan